Van der Waals heterostructure of phosphorene and hexagonal boron nitride： First-principles modeling - 张鹏 王静 段香梅 (Chinese physics B, 2016)
We have studied the structural and electronic properties of a hybrid hexagonal boron nitride with phosphorene nanocomposite using ab initio density functional calculations. It is found that the interaction between the hexagonal boron nitride and phosphorene is dominated by the weak van der Waals interaction, with their own intrinsic electronic properties preserved. Furthermore, the band gap of the nanocomposite is dependent on the interfacial distance. Our results could shed light on the design of new devices based on van der Waals heterostructure.